Transient fungemia caused by an amphotericin B-resistant isolate of Candida haemulonii - Rodero, Laura (2002)
Fil: Rodero, Laura. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Micología; Argentina.